2021
DOI: 10.1038/s41467-021-25022-7
|View full text |Cite
|
Sign up to set email alerts
|

Advancement in long-distance bird migration through individual plasticity in departure

Abstract: Globally, bird migration is occurring earlier in the year, consistent with climate-related changes in breeding resources. Although often attributed to phenotypic plasticity, there is no clear demonstration of long-term population advancement in avian migration through individual plasticity. Using direct observations of bar-tailed godwits (Limosa lapponica) departing New Zealand on a 16,000-km journey to Alaska, we show that migration advanced by six days during 2008–2020, and that within-individual advancement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 74 publications
2
23
1
Order By: Relevance
“…Our empirical and theoretical results align well, and are consistent, with patterns reported in the existing literature on the EAAF migration flyway, which are decreasing trends in total population size along the flyway, increasing trends in population density (Clemens et al, 2016; Piersma et al, 2016; Studds et al, 2017; Wilson et al, 2011; Yang et al, 2011) and increasing stopover duration at the remaining staging area (Conklin et al, 2021). Our study reveals the underlying mechanisms behind a seemingly positive phenomena observed in migratory birds: the increasing counts are likely driven by longer stopover duration, combined with refugees squeezed from other staging sites that have declined in quality, rather than an overall population increase.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our empirical and theoretical results align well, and are consistent, with patterns reported in the existing literature on the EAAF migration flyway, which are decreasing trends in total population size along the flyway, increasing trends in population density (Clemens et al, 2016; Piersma et al, 2016; Studds et al, 2017; Wilson et al, 2011; Yang et al, 2011) and increasing stopover duration at the remaining staging area (Conklin et al, 2021). Our study reveals the underlying mechanisms behind a seemingly positive phenomena observed in migratory birds: the increasing counts are likely driven by longer stopover duration, combined with refugees squeezed from other staging sites that have declined in quality, rather than an overall population increase.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have reported evidence that support parts of the processes we describe here including: longer stopover duration is related to habitat loss, scarce food or high density of competitors (Conklin et al, 2021;Kelly et al, 2002;Moore & Yong, 1991), and decreased refuelling rate causes poor departure body mass in the staging area (Baker et al, 2004), limited refuelling time reducing survival rates in the northward migration (Rakhimberdiev et al, 2018) and (Desprez et al, 2018;Newton, 2006).…”
Section: Empirical Data: Stopover Durationsupporting
confidence: 75%
“…Most of the time series available on migration timing of terrestrial birds show no clear advancements in the timing of migration departure from wintering areas [16,22,[122][123][124]. However, in the last decades, some species of waterfowl and one shorebird have shown profound shifts in timing of departure [123,[125][126][127][128], but these shifts appear mostly linked to changes in suitable stopover sites along their migratory route. At the same time, many terrestrial bird species have advanced timing of arrival in the Arctic, with studies showing species to adjust migration timing to annual variation in climatic conditions in the Arctic [16,22,[129][130][131] and some studies also showing clear trends of advanced arrival over time [22,[132][133][134].…”
Section: Terrestrial and Marine Birdsmentioning
confidence: 99%
“…Yet, our review also highlights potential constraints for animals to make such shifts, which could eventually result in inadequate or no shifts, with possible negative effects on fitness. The potential for animal populations to make shifts in distribution and timing likely relies on the potential for making shifts in migration schedules and strategies, either by individual flexibility [127], or by changes in subsequent generations [225]. In the latter case, the ability of populations to shift in response to a warming climate is linked to its reproductive success under current conditions.…”
Section: Future Outlookmentioning
confidence: 99%
“…While the mechanism underlying adaptive timing remains unclear, prolonged staging at common stopover sites close to the breeding grounds may allow better timing of arrival in respect to climate and food conditions. Such behavior may confound any association between departure from wintering grounds and arrival at breeding grounds, as is the case of spring migrating Bar-tailed Godwits on their way from New Zealand to Alaska (Conklin et al, 2021). The American Golden Plover Spring migration strategies described by Lamarre et al in this topic show an interesting similarity to the Bar-tailed Godwit's strategy.…”
Section: Migration Strategies and Stop-over Ecologymentioning
confidence: 90%